Dementia in Latin America: An Emergent Silent Tsunami - Báez Buitrago, Sandra Jimena (2016)
Recently the Lancet Neurology Commission (Winblad et al., 2016) has provided expert recommendations and highlighted that European Union (EU) is well positioned to take the work lead to prevent and cure the Alzheimer's disease and other dementias, and to provide models for care. This panorama strongly contrasts with the one of Latin America. Although there is an evident growing interest in dementia among Latin American countries (LAC) (Lancet, 2015), important barriers in this region involves big challenges to join the fight against dementia. In this article, we identify some key issues regarding dementia diagnosis that could trigger immediate actions in LAC, contrasting them with the EU scenario (Winblad et al., 2016).